Audio Description and Homoeroticism in the Miniseries Fellow Travelers - Villanueva-Jordán, Iván (Journal of Audiovisual Translation, 2025)
This study analyzes the audio description (AD) of sexual sequences in the television series Fellow Travelers. A central premise of the study is that contemporary telefiction draws from pornographic aesthetics to explore aspects of queer subjectivity and sexuality that earlier television narratives often neglected. To address this complexity, the study aims to complement the traditional narrative approach in AD with two additional approaches: the reflective and affect approaches. While the narrative approach highlights story progression, its limitations in conveying sexual intimacy led to exploring the reflective approach, which draws on gay porn studies to emphasize the symbolic dimensions of queer intimacy. Additionally, the affect approach, informed by Deleuzian film theory (Deleuze, 1986; 2009), considers how close-ups evoke emotional responses. Through a dual analysis—descriptive and prospective—this study proposes strategies to capture affective and symbolic elements, which can expand the potential of AD to address both narrative and subjective dimensions of contemporary queer telefiction. Lay summary This study looks at how sex scenes between two men are described in the audio descriptions of the TV series Fellow Travelers. Audio description (AD) is a service that makes films and shows accessible to blind or visually impaired audiences by narrating what happens on screen. But when it comes to intimate or sexual scenes, the way these moments are described can be tricky. What should be included? What is left out? And how do these choices affect the viewer’s understanding of the story and relationships? Using Fellow Travelers as an example, this research compares existing AD scripts with detailed shot-by-shot breakdowns of scenes. The goal is to find out what is being described, what is omitted, and how this influences the representation of queer intimacy and sexuality. The study highlights three ways to approach AD: the narrative approach, which focuses on the story; the reflective approach, which looks at the cultural and symbolic meanings of sex; and the affect approach, which explores how close-ups, lighting, and movements evoke emotions. The findings show that current AD practices often miss important visual cues—like facial expressions, body movements, or the atmosphere of a scene—that contribute to the emotional and sensual experience of queer intimacy. This study suggests new ways to describe these moments, making AD more inclusive and reflective of the rich, complex stories being told in contemporary queer media.